The impact of morphology on thermal properties and aerobic biodegradation of physically compatibilized poly (lactic acid)/co‐plasticized thermoplastic starch blends. (18th July 2018) - Esmaeili, Mohsen; Pircheraghi, Gholamreza; Bagheri, Reza; Altstädt, Volker
Abstract : Recently, the use of biodegradable polymers became the applicable solution to reduce the environmental concerns, which are created by plastic wastes as well as restrictions of petroleum‐based synthetic polymers. By this point of view, polylactic acid (PLA) as a biodegradable and bio‐based polymer is resolving both aforementioned issues. While, the high cost of PLA and its slow biodegradation rate make researchers to blend it with a faster one, for instance, thermoplastic starch (TPS). Adding TPS into PLA can influence on the morphological structure, thermal stability, and biodegradability. In this study, the well‐tuned co‐plasticized TPS via sorbitol/glycerol mixture was melt mixed with PLA for achieving the physically compatibilized PLA/TPS blend. Thermal properties and aerobic biodegradation behavior of samples were discussed in detail considering the morphology development in each blend composition. Thermogravimetric analysis of PLA/TPS blends showed the single degradation peaks, which indicated the fine interdependence between 2 phases. The continuity and content of TPS phase were strongly influenced on moisture absorption and biodegradability of PLA/TPS samples. Also, the presence of TPS accelerated the biodegradation rate of PLA/TPS samples.